Crystallographic features of oral fluid in young people with gingivitis - S. Vadzyuk; Yu. Boliuk; M. Luchynskyi; V. Sluchyk; W. Zukow (Kazimierz Wielki University, 2020)
Introduction. Oral fluid is involved in maintaining the homeostasis of hard and soft tissues of the oral cavity. Therefore, it can indicate the changes in both the local environment and the whole organism. Recently, the crystallographic features of oral fluid have been actively studied. Therefore, this paper is devoted to the possibility of using crystallographic patterns of oral fluid for the early diagnosis of periodontal diseases in young people under 30 years of age. The purpose of the research is to study the crystallographic picture of oral fluid in subjects aged 18-23 years with gingivitis. Materials and methods. Subjects were divided into two groups: main - with chronic catarrhal gingivitis (28) and control (32). The main group consisted of two subgroups - with mild (18) and moderate (10) gingivitis. The degree of gingivitis was determined using the papillary-marginal-alveolar index (PMA) in Parma modification (1960). The study of oral fluid was performed using the method of wedge-shaped dehydration. The type of crystallization was determined according to the method of Leus P. A. modified by Dubrovina L. A. (1989). Results and discussion. The type II crystallization of oral fluid was observed in the majority of individuals in both groups. Type II of the main group was characterized by massive crystals and minor crystals, smaller in size, and of different shapes. Type III was detected only in subjects with gingivitis. 75,00 % of representatives with mild gingivitis have had type II of crystallization patterns. Again, type III of oral fluid facies was observed only in moderate gingivitis. Conclusions. Dependence of the crystallization type of oral fluid on the severity of the inflammatory process can be used in the development of methods for early diagnosis and prevention of periodontal pathology progression.